Effect of Glucose Syrup and Fish Gelatin on Physicochemical Properties and Oxidative Stability of Spray-Dried Micro-Encapsulated Shrimp Oil - Sirima Takeungwongtrakul; Soottawat Benjakul (My University, 2016)
The effects of different wall materials on micro-encapsulated shrimp oil (MSO) and oxidative stability of MSO during the storage were studied. Whey protein concentrate (WPC), sodium caseinate (SC) and glucose syrup (GS) mixtures at the ratio of either 1:1:2 or 1:1:4 (w/w/w) as wall materials yielded MSO with the highest encapsulation efficiency (EE). When gelatin (GEL) was used to substitute the mixture of WPC : SC, the EE was decreased. The highest EE was obtained when GEL was used to replace WPC. Therefore, SC : GEL : GS (1:1:4) was shown as the most appropriate wall material. After 6 weeks of storage at 30C, MSO with SC : GEL : GS (1:1:4) as wall material had the low peroxide value and the lowest abundance of volatile compounds. Thus, MSO with SC : GEL : GS (1:1:4) as wall material showed the highest EE and enhanced oxidative stability. Practical Applications Shrimp oil from hepatopancreas, is one of the important sources of n–3 fatty acids and carotenoids, which are susceptible to oxidation. Micro-encapsulation with the appropriate wall materials is another potential means in prevention of deterioration of oil mediated by oxidation. Wall material is important in developing micro-encapsulation to enhance oxidative stability of shrimp oil during the extended storage.
Keywords: Gelatin; Peroxide value; Glucose syrup; Peroxide; Microencapsulation and Drying Processes